Cutting dipping application of Flupyradifurone against cassava whiteflies Bemisia tabaci and impact on its parasitism in cassava - Caspary, R.; Wosula, E.N.; Issa, K.A.; Amour, M.; Legg, J. (MDPI, 2023)
The cassava whitefly Bemisia tabaci causes damage in cassava through the feeding and vectoring of plant viruses that cause cassava mosaic and cassava brown streak diseases. This study sought to explore the efficacy of cutting dipping in flupyradifurone for whitefly control and the impact of the mode of application on whitefly parasitism under farmer field conditions. The insecticide treatment significantly reduced adult whiteflies by 41%, nymphs by 64%, and cassava mosaic disease (CMD) incidence by 16% and increased root yield by 49%. The whitefly parasitism rate by Encarsia spp. parasitoids was 27.3 and 21.1%, while Eretmocerus spp. had 26.7 and 18.0% in control and flupyradifurone, respectively, and these differences were not significant. Electropenetrography recordings of whitefly feeding behaviour on flupyradifurone-treated plants showed significantly reduced probing activity and a delay in reaching the phloem as compared to the control. The findings from this study demonstrated that cassava cutting dipping in flupyradifurone significantly reduces whitefly numbers and cassava mosaic disease incidence, thus contributing to a significant root yield increase in cassava. Flupyradifurone applied through cutting dips does not significantly impact parasitism rates in cassava fields. Routine monitoring of parasitoids and predators in insecticide-treated versus control fields should be emphasized to determine the impact of pesticides on these beneficial non-target organisms.